Capacitive Sensors for the Long-wave Acoustic Radiation by Directed Waves - L.V. Zaitseva (Журнал нано- та електронної фізики)
Consider from the common position present-day state, prospects and the possibility of non-destructive testing capacitive method using. Developed mathematical model of the process of acoustic wave’s excitation (longitudinal and surface) with a capacitor allow carrying out the output signal calculation for the subsequent choice of methods and devices for receiving the acoustic oscillations data. A device layout has been developed for realization of capacitive method. The possibility of excitation and reception of acoustic vibrations by capacitive transducers it has been established.